Metabolism Analysis in Mice with Reduced Citrate Synthase Activity (Baltic Journal of Sport and Health Sciences, 2017)
Background.  Citrate  synthase  (CS)  plays  an  important  role  in  the  regulation  of  carbohydrate  oxidation. Variation in citrate synthase activity has an influence on metabolic changes. We tested the hypothesis that reduced mitochondrial CS activity could affect energy expenditure (EE) and respiratory quotient (RQ) in mouse model with an emphasizing on gender differences between tested strains.Methods. 16-week of age wild-type C57Bl/6J (B6) mouse strain, B6.A-(rs3676616-D10Utsw1)/Kjn (B6.A) and C57BL/6J-Chr 10A/J/NaJ (B6.A10) strains with reduced CS activity were studied in physiocage by the “Panlab” metabolism analysing equipment. The following parameters were calculated: EE (ml/min/kg^0.75), RQ, physical activity and rearing. Results. In female mice EE values were lower in B6.A10 strain compared to wild-type B6 strain. RQ values were similar in all tested mouse strains. In B6 mice EE was higher in females compared to males. Rearing was elevated in females of B6 mice compared to males.Conclusions. EE was lower in B6.A10 compared to B6 mice. Gender differences were noticed only in B6 mice: EE and rearing were significantly higher in female compared to male mice. Current study did not reveal any other association between reduced CS activity and EE or RQ variation in male and female mice.Keywords:  energy expenditure, respiratory quotient, physical activity, gender effect.